Bariery powstawania i rozwoju klastrów w Polsce - Zbadyński, Mariusz (Cluster Formation and Development Barriers in Poland, 2007)
Modem concepts of regional development connected with such features as those of forming networks, clusters of enterprises, etc. assume that creating the best conditions for innovative regional development is possible only by the union of forces of various types of its participants: such as their enterprises, self-government, supporting institutions and research institutions. The greatest barrier to cluster formation and development in Poland is the absence of cooperation among companies, also considered as one of the lingering factors of communism. The main cause of these situations is approach the lack of knowledge about the clusters of enterprises and the fear of own enterprises. The lack of these proinnovations mechanisms in Poland like cluster is causing a situation where enterprises do not introduce innovations on the expected scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 122-130